(untitled) (Journal of Engineering, 2013)
In this paper flotation method experiments were performed to investigate the removal of lead and zinc. Various parameters such as pH, air flow rate, collector concentrations, collector type and initial metal concentrations were tested in a bubble column of 6 cm inside diameter. High recoveries of the two metals have been obtained by applying the foam flotation process, and at relatively short time 45 minutes . The results show that the best removal of lead about 95% was achieved at pH value of 8 and the best removal of zinc about 93% was achieved at pH value of 10 by using 100 mg/l of Sodium dodecylsulfate (SDS) as a collector and 1% ethanol as a frother. The results show that the removal efficiency increased with increasing initial metal concentrations in the alkaline conditions while it decreased in the acidic condition. Increasing air flow rate up to 1000 ml/min enhanced the separation efficiency. Selective flotation experiments were also conducted in the presence of metalion mixture solutions. It was possible to separate lead and zinc under suitable condition, successful removals reached about 84% and 81% for lead and zinc respectively . It was observed that the first order equation fitted the data as good and better than any of the other equations.